We never talk about our work in this way : a practice-led exploration of the experiences of applied drama and theatre practitioners working in Gauteng and the Western Cape - Qhobela, Lireko Pearl (Stellenbosch : Stellenbosch University, 2023)
Thesis (DPhil)--Stellenbosch University, 2023.